(untitled) (In situ, 2024)
Stone monuments to the departed (mirila) from Rtina are located in the western part of Ražanac, behind Gajetovica. They are one of the three groups of these stone monuments in Ražanac Municipality, and are related to the mortuary practice associated with the transfer of the deceased from Rtina. They were erected on the way to the old cemetery, which was located near the modern monument in Ražanac.